Linguistic Intelligence in Arabic Learning in Islamic Religious College Students - Hilmi, Danial; Toifah, Nur; Sa’diyah, Halimatus (Ta’lim al-’Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2024)
This study aims to analyze the linguistic intelligence of students learning Arabic in Islamic universities in Indonesia. The study used a quantitative approach with descriptive research methods, and data were collected through a questionnaire distributed to 264 UIN Maulana Malik Ibrahim Malang and 125 students UIN Antasari Banjarmasin students using random sampling techniques. The findings reveal that at UIN Maulana Malik Ibrahim Malang, 34% of the students demonstrated dominant linguistic intelligence, 48% exhibited standard linguistic intelligence, and 18% showed low linguistic intelligence. Similarly, at UIN Antasari Banjarmasin, 34% of the students displayed dominant linguistic intelligence, 53% demonstrated standard linguistic intelligence, and 13% exhibited low linguistic intelligence. These results highlight the importance of addressing variations in linguistic intelligence levels among students in Arabic language education. The practical implications suggest that educators at Islamic universities should design teaching and learning strategies that accommodate these differences, fostering the development of student’s interests and talents through appropriate learning systems and methodologies. Future researchers are encouraged to explore linguistic intelligence using qualitative approaches to gain deeper insights into students’ learning experiences